Retinal nerve fiber layer and macular thickness in amblyopia as measured by spectral domain optical coherence tomography - Al-Haddad, Christiane E. (2011)
Background/aims To study peripapillary retinal nerve fibre layer (RNFL) and macular thickness in amblyopia using high-definition spectral-domain optical coherence tomography (SD-OCT) and to compare the results with available literature using the time-domain modality. Methods This was a prospective institutional study of patients ≥6 years of age with unilateral amblyopia (strabismic or anisometropic) and non-amblyopic anisometropia. RNFL and macular thicknesses were measured using SD-OCT and compared between fellow eyes. Results The mean age was 20 (±12) years; 45 patients had amblyopia: 14 strabismic and 31 anisometropic. 20 patients had non-amblyopic anisometropia. The mean macular thickness was significantly increased in the amblyopic (273.8 μm) vs fellow eyes (257.9 μm), p=0.001. This difference remained significant in the anisometropic group (p=0.002) but not the strabismic group. The mean RNFL thickness was similar in amblyopic (95.4 μm) and fellow eyes (94.0 μm). Similar results were obtained regardless of the level of visual acuity, age or refractive error. In the control group of non-amblyopic anisometropia, the interocular difference did not reach statistical significance. Conclusions Central macular thickness was significantly increased in anisometropic amblyopia using SD-OCT. Anisometropia alone did not produce such a difference, which points to a possible correlation between amblyopia and the development of the retinal layers.